IMPACT OF E-SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER SATISFACTION ON POSAJA! APPLICATION - Muhammad Zaky Hidayatullah; Riski Taufik Hidayah (SEAN Institute, 2023)
Along with the times, business and technology have become interrelated. Technology has a significant role in running a business, for example, with e-commerce. The increasing growth of e-commerce in Indonesia has positively and significantly impacted freight forwarders and logistics companies with the emergence of newcomers. According to Supply Chain Indonesia (SCI), in 2022, performance in the logistics sector, including expeditions, will improve. SCI also projects that the logistics sector has contributed to Indonesia's GDP in the last two years. The logistics industry in Indonesia has been growing since the existence of e-commerce. Indonesia has the largest e-commerce market in Southeast Asia, with almost 100% mobile traffic. With all this increasing growth, shipping service companies must digitize their services by utilizing technology, especially applications. This study aims to see the effect of the E-Service Quality and Customer Value variables on Customer Satisfaction in the PosAja application. This quantitative study collects data through questionnaires and analyzes data using PLS-SEM with SmartPLS 3 software. This study uses primary and secondary data by determining the Indonesian population who have used or are currently using the PosAja application. Sampling in this study used a non-probability sampling technique with a purposive sampling method and produced 120 respondents using Gpower 3.1.9.7. The results show that e-service quality and customer value significantly affect customer satisfaction. And customer value provides a good mediating role for these two variables.